2017
DOI: 10.1002/asia.201700766
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Cyclization of (o‐Alkylbenzoyl)phosphonates to Benzocyclobutenols

Abstract: (o-Alkylbenzoyl)phosphonates readily cyclize to highly strained benzocyclobutenols simply upon irradiation with UV light. The remarkable efficiency is ascribed to the electron-accepting character of the phosphonate substituent, which facilitates thermal ring closing of the o-quinodimethane intermediate and suppresses reversion to the starting carbonyl compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Here, we report a new, two-step procedure to synthesize benzocyclobutenones through visible light induced cyclization of ( o -alkylbenzoyl)­phosphonates that we have recently developed . An H-phosphonate assumes a key role as the recyclable auxiliary; the H-phosphonate is readily introduced onto aroyl chlorides, facilitates visible light induced construction of the four-membered ring skeletons, and is removed for regeneration of a carbonyl group, recovered, and reused.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we report a new, two-step procedure to synthesize benzocyclobutenones through visible light induced cyclization of ( o -alkylbenzoyl)­phosphonates that we have recently developed . An H-phosphonate assumes a key role as the recyclable auxiliary; the H-phosphonate is readily introduced onto aroyl chlorides, facilitates visible light induced construction of the four-membered ring skeletons, and is removed for regeneration of a carbonyl group, recovered, and reused.…”
mentioning
confidence: 99%
“…We recently reported that the photoinduced cyclization of ( o -alkylbenzoyl)­phosphonates 1 forming phosphonate-substituted benzocyclobutenols 4 is far more efficient and reproducible than that of ordinary ketones (Scheme ). The origin of the efficiency is mainly ascribed to the electron-accepting nature of the phosphonate substituent. The key intermediate to form a four-membered ring by 4π-electron cyclization is o -quinodimethane 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation